Predictors of work productivity in adults schizophrenia: a scoping review - Anjani Mutiarasani; Suryani Suryani; Imas Rafiyah (Poltekkes Kemenkes Bandung, 2026)
Background: Schizophrenia is a chronic mental disorder that substantially impairs social functioning and work productivity, leading to high unemployment rates and significant economic burdens for individuals, families, and society. Despite the importance of employment for recovery and quality of life, evidence regarding the predictors of work productivity among individuals with schizophrenia remains fragmented. Objective: This scoping review aimed to identify and map key factors associated with work productivity in individuals with schizophrenia. Methods: The review was conducted following the PRISMA-ScR guidelines. A comprehensive literature search was performed across four electronic databases, including Google Scholar, Scopus, PubMed, and EBSCO. The search was limited to articles published between 2015 and 2025. Results: After systematic screening and feasibility assessment of 1,307, 10 studies were included in the final analysis, consisting of various research designs such as cross-sectional, longitudinal, cohort, randomized controlled trials, and case reports. The findings indicate that work productivity in individuals with schizophrenia is influenced by four main domains: cognitive function, motivation and psychological factors, family and social support, and work rehabilitation interventions. Conclusion: The findings work productivity among adults with schizophrenia is influenced by multiple interrelated factors, particularly cognitive function, motivation, family and social support, quality of life, and work rehabilitation. These findings support multidimensional assessment in clinical settings and recovery-oriented support in community and rehabilitation services to improve vocational outcomes.